Prediction of Water Yield of Mount Banahaw Watersheds in Quezon Province, Philippines Using Hydrologic Water Balance Model - Moses T. Macalino; Putu Sudira; Sahid Susanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2000)
-